The Influence of Vermicompost and Various Concentrations of Lead on the Enzymatic Activity of Sierozem Soils of Kazakhstan - G. A. Sainova; N. A. Kaliyeva; D. Kh Yuldashbek; A. D. Akbasova (Scientifica)
The influence of vermicompost and various concentrations of lead on the activity of hydrolytic (urease and protease) and oxidative-reducing (catalase and dehydrogenase) enzymes in the sierozem soil of Southern Kazakhstan (Turkestan region) was studied. Background unpolluted soils served as a control. The work shows a change in the enzymatic potential when vermicompost (8 t/ha) and lead are introduced into the soil in the concentration range of 16 to 160 mg/kg Pb. As a result of experimental studies, a decrease in the activities of catalase, protease, and dehydrogenase and, conversely, an increase in the activity of urease with an increase in the lead content in the soil system were revealed. Introduction of vermicompost (vermicompost) into the soil caused an increase in the activity of all studied enzymes and a decrease in the translocation ability of Pb. Inhibition of the process of translocation of lead into plants by vermicompost creates conditions for obtaining environmentally friendly agricultural products.